Firbush 2001 (Res Medica, 2014)
Perhaps not content with the absence of climbing from the weekend activities several of the residents displayed their agility with a show of table mountaineering. Meanwhile Simon was determined that Andy enjoy a nocturnal swim in the lake. His lack of subtlety, approaching Andy brandishing a luggage strap perhaps gave him away and another Finch masterplan was foiled. As the windsurfers devised some masochistic game involving using newspaper clubs to beat each other I retired to my quarters.Firbush, situated on the south bank of Loch Tay, has been home to the University’s Centre for Sport and Exercise outdoor centre for around 30 years. The outward, moderate log cabin appearance masks a well furnished an equipped interior (no telly - but you can see a satellite picture of weather in Africa though!). It primarily caters for weekday reading parties and weekend clubs and societies. This weekend the RMS were joined by the windsurfing club.